Lower extremity sarcoma mimicking acute compartment syndrome. (March 2015) - Marlborough, F.; Venkataraman, R.
Abstract: Compartment syndrome is defined as an increase in interstitial fluid pressure within an osseofascial compartment leading to microcirculatory compromise and myoneural necrosis. Common causes include trauma, reperfusion injury, compressive casts, crush injuries and burns. Other rare causes of compartment syndrome such as tumours and ruptured Baker's cyst have been reported in literature sporadically. We present a patient who presented with clinically convincing symptoms and signs of a compartment syndrome in the leg secondary to a high-grade sarcoma in the calf musculature with a coexisting large ruptured Baker's cyst.